Indoor radon and airborne particles - L. Godínez (Geofísica Internacional, 2002)
Daily radon fluctuations were monitored in dwellings located in the State of Mexico and in Mexico City in order to assessthe expected fluctuations in a short term monitoring basis. The radon monitoring was performed with Honeywell A9000 A devicesthat record radon and daughters using silicon detectors. Airborne particle fluctuations were also determined using a Personal Data-Logging Real-time Aerosol Monitor. The results indicate an indoor radon average value of 22 Bq/m3. Discrete values one order ofmagnitude higher than the mean were observed, mainly between midnight and early morning. The airborne particles in the bedroomshowed daily average values of 0.08 mg/m3. Experiments with smokers indicated fluctuations in the airborne particle concentrationsthat depend on the ventilation and the number of smokers in the room.